1988
DOI: 10.1128/mcb.8.1.169
|View full text |Cite
|
Sign up to set email alerts
|

The accumulation of three yeast ribosomal proteins under conditions of excess mRNA is determined primarily by fast protein decay.

Abstract: The suggestion that compensation for overabundant mRNA of the genes for Saccharomyces cerevisiae ribosomal protein (r-protein) L3, L29, or rp59 occurs by translation repression has been reinvestigated. First, analysis of the distribution of these three mRNAs in polysome profiles revealed no differences between normal and mRNA-overproducing strains, indicating that initiation of r-protein translation is not repressed under conditions of mRNA overaccumulation. Second, experiments involving radioactive pulse-labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 36 publications
6
67
0
Order By: Relevance
“…The growth rate dependence of protein synthesis is also reflected in changes in the concentration of rRNA and ribosomal proteins (r-proteins). Because r-proteins are synthesized in excess of what can be assembled into ribosomes (Warner et al, 1985;Maicas et al, 1988), r-proteins represent a major class of short-lived proteins, with half-lives of 1-5 min (Warner, 1989). Therefore, r-proteins represent a second major class of Ssb1/2p substrates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth rate dependence of protein synthesis is also reflected in changes in the concentration of rRNA and ribosomal proteins (r-proteins). Because r-proteins are synthesized in excess of what can be assembled into ribosomes (Warner et al, 1985;Maicas et al, 1988), r-proteins represent a major class of short-lived proteins, with half-lives of 1-5 min (Warner, 1989). Therefore, r-proteins represent a second major class of Ssb1/2p substrates.…”
Section: Discussionmentioning
confidence: 99%
“…In E. coli, some of this regulation is achieved by transcriptional attenuation and translational regulation via binding of ribosomal proteins to the RNAs of target operons (Freedman et al, 1985;Cole and Nomura, 1986). In yeast, regulation is partly transcriptional, via RAP1 and its binding site, the upstream activating sequence (UAS) rpg (Herruer et al, 1987;Moehle and Hinnebusch, 1991;Kraakman et al, 1993), although much of the regulation of ribosomal protein abundance is achieved by a competition between the assembly into ribosomes and the rapid degradation of unassembled ribosomal proteins (Warner et al, 1985;Maicas et al, 1988).Growth rate control clearly modulates the level of the translational machinery, which in turn influences the overall rate of protein synthesis. Changes in the rates of protein synthesis must, in turn, have profound implications for the protein chaperone system.…”
mentioning
confidence: 99%
“…Most RPs are very basic (pI > 10), so at high concentrations they might bind nonspecifically to chromatin. Previous studies, however, have indicated that mechanisms that rapidly degrade excess RPs tend to keep the cellular concentrations of free RPs low (Warner 1977(Warner , 1989Maicas et al 1988;Lam et al 2007;Perry 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In eukaryotic cells and particularly in yeast, balanced expression of ribosomal proteins is mainly achieved at the post-transcriptional level and, more specifically, through the regulated turnover of ribosomal proteins (elBaradi et al 1986;Maicas et al 1988;Tsay et al 1988). Thus, individual ribosomal proteins that are present in excess in the cell are rapidly degraded until they reach levels identical to other ribosomal proteins (elBaradi et al 1986;Maicas et al 1988;Tsay et al 1988). The hrpS5 coding sequence was therefore cloned into the high copy number 2m vector to ensure high level hrpS5 expression; the assumption that putative excess hrpS5 would be degraded to maintain hrpS5 at the same level in the mutant strain as yrpS5 in the WT strain was confirmed by Western blotting (see below).…”
Section: Human Rps5 Substitutes For Its Yeast Homolog In Vivomentioning
confidence: 99%